Produção científica em políticas públicas educacionais de Moçambique - Muara, Julio Magido Velho (Universidade do Vale do Rio dos Sinos, 2020)
The thesis has as its theme the Scientific Production in Public Educational Policies of Mozambique. The research analyzes 60 scientific works, being 43 dissertations and 17 thesis, which approach themes on educational policies, defended by Mozambican with postgraduate degree, in the period of 2000 and 2018, explaining the development and the main trends, evidencing its dynamics in the research field in this time frame. It is a study that has to do with State-of-the-art. Methodologically the research is of descriptiveexploratory character with qualitative approach. Incorporates two fundamental parts: the first contextualize the three historical moments of Mozambican society (pre-colonial, colonial and post-independence), it looks especially at political-historic context of the last two moments. It was emphasized the political influence on the produced research and mentioned all the education metamorphoses, of scientific research and of higher education of that followed in different political moments. The second part analyses the dissertations and thesis summaries examining the discussed aspects, considering the conceptions, approaches and subjacent tendencies. A few part of the cases where the summary was not clear, was done the exploratory reading of introduction and conclusions. We determinate the thematic categories of researches which will permit the visualization of the prominent educational policies and the more analyzed by the researchers, which may be: Educational Management Policies; Teacher’s Training Policies; Policies related to School councils and, finally, the policies regarding to the opportunities and educational inequality. As the integrated part of analysis, in the domain of this research, it was created an Institutional repertoire charged by High Institute of Health Science [Mozambique]. In conclusion, we perceive that the Educational Research in Mozambique it was always permeated by the environment and accompanied by the disputes of Political Power. Among the obtained results it was possible to see the emphases in the research conceptions and tendencies and in equal way it was possible to perceive that all the researches bring subsidies for the action and intervention in the reality scenery of school, in political- pedagogic quality and in the formation of school system. Together in the final considerations, the research ends with meta-analysis – a reflexive movement of metacomprehension of Mozambican Research in Educational policies.
Keywords: Pesquisa em educação; Estado da arte; Metanálise; Education research; State-of-the-art; Meta-analysis; ACCNPQ::Ciências Humanas::Educação